Infant with sudden, large, post-extubation subglottic cyst - Asha'ari, Zamzil Amin; Suhaimi, Yusof; Fadzil, Ahmad (UKM, 2012)
Background: Subglottic cyst in infancy is almost always associated with episodes of early life intubation. Most cases typically presented late, usually days to months after endotracheal extubation. We report a case of a subglottic cyst with different presentation than the norm.